Comparative analysis of heteropyknotic chromatin and silver-stained material in Platycarenus umbractulatus (Pentatomidae: Discocephalinae) - Souza, Hederson Vinicius [UNESP]; Itoyama, Mary Massumi [UNESP] (Int Science Services/balaban Publishers, 2011)
The genus Platycarenus is an unusual member of the subfamily Discocephalinae because it does not have a harlequin lobe. To gather information on this genus, a comparative analysis of heteropyknotic chromatin and silver-stained material was carried out in Platycarenus umbractulatus F. (Pentatomidae: Discocephalinae). The testicular lobes were analyzed separately, and meiotic behavior in the seven lobes was found to be similar, i.e., no difference in the meiotic process between the lobes. Major differences were detected during spermiogenesis. Cells of lobes I, 2, 3, and 7 had similar characteristics, as did lobes 4 and 6, but there were differences between these two groups. The differences between these lobes were in the concentration and location of heteropyknotic chromatin and the amount of silver-stained material. Lobe 5 showed significant differences in comparison with interlobular and intralobular spermatids. Therefore, the results of P. umbractulatus indicate that, although this species does not possess a harlequin lobe, it has differentiated characteristics not yet reported in the literature. Also, a close association of the chromocenter with the nucleolus was demonstrated; it was possible to establish the involvement of sex chromosomes in the formation of the nucleolus. Thus, this study provided insights into the involvement of heteropyknotic chromatin with the nucleolus and also showed the possibility of characterizing the evolution of sperm with a non-fertile function, where more accurate exploration of this theme with other approaches is evident.
Keywords: Spermatogenesis; Spermiogenesis; harlequin; Nucleolus; Testicular lobes